An Investigation of the Transdiagnostic Model of Eating Disorders in the Context of Muscle Dysmorphia. (2nd August 2012) - Murray, Stuart B.; Rieger, Elizabeth; Karlov, Lisa; Touyz, Stephen W.
Abstract Aim Muscle dysmorphia is a psychiatric disorder that has been conceptually linked to eating disorders, although its precise nosology remains unclear. To further investigate this notion, the present study examined the applicability of the transdiagnostic model of eating disorders to muscle dysmorphia. Method One hundred and nineteen male undergraduate students completed self‐report measures of multidimensional perfectionism, mood intolerance, self‐esteem, interpersonal problems, and muscle dysmorphia symptomatology. Results Self‐oriented perfectionism, socially prescribed perfectionism, mood intolerance, and low self‐esteem significantly predicted muscle dysmorphia symptomatology, whereas other‐oriented perfectionism and interpersonal problems did not demonstrate significant predictive value when accounting for the other transdiagnostic constructs. Discussion The transdiagnostic model of eating disorders may potentially be applied to enhance our understanding of the maintenance of muscle dysmorphic features in addition to eating disorder symptomatology. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.